Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1183/13993003.00062-2022
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory hyperoxia suppresses lung cancer metastasis through a MYC/SLC1A5-dependent metabolic pathway

Abstract: The lack of knowledge about the effect of inspiratory hyperoxia on the lung-specific tumour microenvironment and progression of lung cancer has attracted considerable attention. This study proposes that inspiratory hyperoxia has special significance for the malignant phenotype of lung cancer cells. The effects of different oxygenation parameters on the proliferation, apoptosis, invasion and migration of lung cancer cells were systematically evaluatedin vitroandin vivo. Our results reveal that inspiratory hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…296 Liu demonstrated that intracellular metabolic reprogramming driven by the MYC/SLC1A5 axis is the main mechanism by which hyperoxia (60% O 2 , 6 h/day) inhibits lung cancer metastasis. 297 The antitumor effect of atmospheric hyperoxia may be due to oxidative stress and increased apoptosis (BCL2-associated X [Bax]/Bcl-2 mRNA expression rate), which is associated with the mitogen-activated protein kinase (MAPK) pathway. 298,299 In the early stage, the antitumor effect of hyperoxia therapy was mainly studied in lung tumors.…”
Section: Hyperoxia Therapy In Pulmonary Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…296 Liu demonstrated that intracellular metabolic reprogramming driven by the MYC/SLC1A5 axis is the main mechanism by which hyperoxia (60% O 2 , 6 h/day) inhibits lung cancer metastasis. 297 The antitumor effect of atmospheric hyperoxia may be due to oxidative stress and increased apoptosis (BCL2-associated X [Bax]/Bcl-2 mRNA expression rate), which is associated with the mitogen-activated protein kinase (MAPK) pathway. 298,299 In the early stage, the antitumor effect of hyperoxia therapy was mainly studied in lung tumors.…”
Section: Hyperoxia Therapy In Pulmonary Cancermentioning
confidence: 99%
“…Exposure to hyperoxia before or after drug administration usually promotes tumor development, and further exposure to hyperoxia for a period of time begins to suppress tumor development, but the specific mechanism has not been deeply explored 296 . Liu demonstrated that intracellular metabolic reprogramming driven by the MYC/SLC1A5 axis is the main mechanism by which hyperoxia (60% O 2 , 6 h/day) inhibits lung cancer metastasis 297 . The antitumor effect of atmospheric hyperoxia may be due to oxidative stress and increased apoptosis (BCL2‐associated X [Bax]/Bcl‐2 mRNA expression rate), which is associated with the mitogen‐activated protein kinase (MAPK) pathway 298,299 .…”
Section: Antitumor Effects Of Hyperoxia Therapymentioning
confidence: 99%
“…Subsequently, the microarray was incubated with horseradish peroxidase (HRP) polymer-conjugated secondary antibody and stained with 3, 3-diaminobenzidine solution and hematoxylin. The staining intensity score was rated as previously reported [ 18 ]. Briefly, the immunohistochemical staining intensity scores of HOMER3 were evaluated by combining the percentage of immunostained cells with the staining intensity.…”
Section: Methodsmentioning
confidence: 99%
“…The extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) were measured using an Agilent Seahorse XFe96 extracellular flux analyzer (Agilent Technologies Inc.) as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…During hyperoxia (60% oxygen), MYC expression is decreased which leads to the downregulation of its downstream target gene, SLC1A5 . Then, the disturbance in glutamine uptake and catabolism, and inhibition of invasion and metastasis is happened [ 54 ]. Also, the results of a study by Alfarsi et al.…”
Section: Slcs In Cancermentioning
confidence: 99%